Maritime Geographie: Die Stellung der Geographie des Meeres und ihre Aufgaben im Rahmen der Meeresforschung - Paffen, Karlheinz (ERDKUNDE, 1964)
With reference to both the memoranda of the Deutsche Forschungsgemeinschaft (Central German Research Board) about the state of marine research and geography in Germany, the place and tasks of a marine geography are sketched. Starting from the fact that the earth’s surface consists of 361 mill, sq.km. of seas and 151 mill, sq.km. of land, and from the present situation where geography is almost exclusively concerned with the continents only, the question of why geography has largely turned its back on marine-geographical problems is answered by a historical recollection of the relationships between geography and oceanography since the turn of the century. After the emancipation of oceanography as a discipline of geophysics, geography has been unable until the present to close the gap thus originated. However, since the world oceans are the second major group of phenomena of the earth’s surface, and nearly two and a half times as large as the land surfaces, geography should accord them equal attention as intensive and comprehensive as that give to the continents. Since the world oceans differ in many respects so greatly from the land surfaces they should best be treated in a marine geography which gathers together all geographical problems of the oceanic sphere. Corresponding to the dual nature and the scientific system of modern geography marine geography has the following tasks outlined below. These should also give to the subject within the framework of general international marine research as represented by the Scientific Committee on Oceanic Research (S. C. O. R.), a co operative body of many different disciplines, a more important, in certain respects even an integrating position.